COVID-19: a potential driver of immune-mediated breast cancer recurrence? - Francescangeli, Federica (Breast Cancer Res, 2020)
Severe coronavirus disease 2019 (COVID-19) causes a hyperactivation of immune cells, resulting in lung inflammation. Recent studies showed that COVID-19 induces the production of factors previously implicated in the reawakening of dormant breast cancer cells such as neutrophil extracellular traps (NETs). The presence of NETs and of a pro-inflammatory microenvironment may therefore promote breast cancer reactivation, increasing the risk of pulmonary metastasis. Further studies will be required to confirm the link between COVID-19 and cancer recurrence. However, an increased awareness on the potential risks for breast cancer patients with COVID-19 may lead to improved treatment strategies to prevent metastatic relapse.